2021
DOI: 10.3390/ijerph182312582
|View full text |Cite
|
Sign up to set email alerts
|

Online Training in Accessibility and Design for All: A Tool to Train Post-COVID Inclusive Graduates

Abstract: Agenda 2030 expresses, through the Sustainable Development Goals (SDG), and in particular through No. 4, the need to ensure an inclusive and equitable education, which promotes learning opportunities for all. At the university level, all students are urged to acquire the necessary theoretical and practical knowledge to promote sustainable development, so that they become graduates capable of facing the challenges of the future and the real demands of a society marked by heterogeneity, including the needs of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Therefore, the perception of public health's educational effectiveness via online training should be measured using the knowledge, skill, and attitude learned during training. Further, several researchers, including Talati et al (2018); Moreno-Rodriguez et al (2021); McKay et al (2022) have evaluated online training effectiveness using scores of learning perception by comparing the pre-and post-evaluation; in which, their findings indicated that online training was effective when there was a significant increase of learning between preand post-training evaluation. This is consistent with Kirkpatrick (1996); Kraiger et al (1993) suggestion to evaluate training effectiveness by comparing the pre-and post-training evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the perception of public health's educational effectiveness via online training should be measured using the knowledge, skill, and attitude learned during training. Further, several researchers, including Talati et al (2018); Moreno-Rodriguez et al (2021); McKay et al (2022) have evaluated online training effectiveness using scores of learning perception by comparing the pre-and post-evaluation; in which, their findings indicated that online training was effective when there was a significant increase of learning between preand post-training evaluation. This is consistent with Kirkpatrick (1996); Kraiger et al (1993) suggestion to evaluate training effectiveness by comparing the pre-and post-training evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors claim that this approach could ensure inclusive and equitable quality education for all. An analysis to explore design criteria for learning applications that favor the learning process and meet the needs of people with disabilities, equal opportunities, and universal accessibility was conducted by [37]. In another work [38], the e-learning experiences of deaf learners during the pandemics are investigated.…”
Section: Related Work and Backgroundmentioning
confidence: 99%
“…The second consideration from which the present work is developed is from the empirical experience developed by the authors themselves, who in different works already published analyze one by one the aspects referred to by the Sustainable Development Solutions Network for the achievement of SDG4 in higher education institutions, as well as in other recent empirical works that highlight specific recommendations, such as those of Díaz-Vega et al (2020, Moreno-Rodríguez et al (2021), CERMI (2020), Madrid et al (2020, as well as in technical documents of organizations, such as the United Nations, UNESCO, the Spanish Network for Sustainable Development, or the United Nations Development Program, aimed at the implementation of the 2030 Agenda in the university environment.…”
Section: Introduction University and Agenda 2030mentioning
confidence: 99%